UNAVAILBILITY OF APPROPRIATE DOSES AND NEED FOR TABLET SPLITTING OF PSYCHOTROPIC DRUGS BY GERIATRIC PATIENTS - Flávio Mascarenhas Starling; Einstein Francisco Camargos; Felipe Ferreira; Marco Polo Dias Freitas; José Reinaldo Silva Costa; Patrícia Medeiros-Souza (Brazilian Society of Geriatrics and Gerontology, 2020)
BACKGROUND: Tablet splitting appears common in older adults, but its safety, and the factors associated with this practice, remain unclear. OBJECTIVE: To identify which psychotropic drugs are most often split, which doses are intended with this practice, and whether these doses are provided by the Brazilian Unified Health System (SUS) or commercially available. METHODS: Cross-sectional descriptive study of 632 geriatric outpatients. The number of individuals who split tablets was identified, as well as the psychotropic drugs they used and split. The availability of these drugs on the SUS network and on the market was assessed by checking the 2017 National Formulary of Essential Medicines (RENAME 2017) and the Dictionary of Proprietary Medicinal Products (Dicionário de Especialidades Farmacêuticas) respectively. RESULTS: Tablet splitting was reported by 178 patients (28.2%). This practice was significantly more common among those aged 80 years or older. Tablet splitting was significantly associated with a greater number of medical visits and a higher pill burden. The most commonly affected therapeutic classes were antipsychotics (23.9%), other psychotropic drugs (18.7%) and antidepressants (12.3%). Of the 20 psychotropic drugs split, 45% were available on the SUS. CONCLUSIONS: Tablet splitting poses a challenge, as there is no guarantee of uniformity of concentration of the active ingredient in the split halves. Although the psychotropic drugs that were split in this sample are commercially available, most were not available from SUS in the desired dose forms for older adults.